A decrease in serum 1, 5‐anhydroglucitol levels is associated with the presence of a first‐degree family history of diabetes in a Chinese population with normal glucose tolerance. Issue 1 (13th November 2017) - Hu, X.; He, X.; Ma, X.; Su, H.; Ying, L.; Peng, J.; Wang, Y.; Bao, Y.; Zhou, J.; Jia, W.
Abstract: Aim: This study aimed to investigate alterations in HbA1c, glycated albumin (GA) and 1, 5‐anhydroglucitol (1, 5‐AG) in Chinese first‐degree relatives of individuals with diabetes (FDR) in pursuit of an index for early screening of glucose metabolism disturbance. Methods: A total of 467 participants (age range: 20–78 years) with normal weight and normal glucose tolerance, as determined by a 75‐g oral glucose tolerance test, were enrolled. HbA1c was measured using high‐performance liquid chromatography. Serum GA and 1, 5‐AG levels were determined by enzymatic methods. Serum insulin levels were measured using an electrochemiluminescence immunoassay. Results: The study population included 208 FDR and 259 non‐FDR. Serum 1, 5‐AG levels were lower in FDR than that in non‐FDR (20.4 ± 7.5 vs 23.8 ± 8.3 μg/ml, P < 0.001), but HbA1c and GA levels did not differ between them ( P = 0.835 and 0.469, respectively). Logistic regression analysis revealed an independent relationship between a first‐degree family history of diabetes and reduced serum 1, 5‐AG levels (odds ratio = 0.944, P < 0.001). Multiple regression analysis showed that a first‐degree family history of diabetes ( β = –3.041, P < 0.001) and insulinogenic index ( β = 0.081, P = 0.001) were independently associated with serum 1, 5‐AG levels. Conclusion: In a Chinese population with normal glucose tolerance, serum 1, 5‐AG levels were lower among FDR, and serum 1, 5‐AG levels were independently associated with FDR status. For FDR, serum 1, 5‐AG levels were more sensitive than HbA1c or GA levels to early‐phase abnormality in glucose metabolism. What's new?: This is the first evidence in a Chinese population that serum 1, 5‐anhydroglucitol levels were decreased significantly in individuals with a first‐degree family history of diabetes. Serum 1, 5‐anhydroglucitol levels were independently associated with a family history of diabetes in individuals with normal glucose tolerance based on an oral glucose tolerance test. Serum 1, 5‐anhydroglucitol levels were more sensitive to early‐phase abnormality in glucose metabolism than HbA1c and glycated albumin levels. For the high‐risk population with genetic susceptibility to diabetes, serum 1, 5‐anhydroglucitol levels can serve as a sensitive and convenient biomarker for monitoring early‐stage glucose intolerance.